(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2010)
The contributions in this volume foreground issues in the areas of philosophy, civilisation, history and discourse. They are concerned with universal issues as well as local matters. The first article looks at the universal issue of human emotion, particularly emotion and woman. The author, in her discussion, follows Edith Stein who argues that the biological and maternal nature of woman affects her whole being. Stein's philosophy underlines two characteristics of woman, attraction to the personal and attraction to wholeness, which make her sensitive towards her own being and others. The author sees Stein's philosophy as ''a remarkably deep source of enlightenment'' which challenges recurrent assertions of emotion as an unreasonable phenomenon and of woman as the 'weaker sex'. The second article is an examination of the role of the concept of sustainable development in developing a sustainable society. It argues for religious awareness and moral guidance in instilling the values of protecting and caring for the environment, and natural resources that will help generate a civilized society, one that understands the interdependence between human and the environment for sustainability. The third and fourth papers are both historical in nature as they consider local issues based on historical documents. The former is concerned with issues surrounding the Malay Reservation Enactment that was created in Malaya in the early 1900s to safeguard Malay-owned land. The latter is a historical account of the Suara Rakyat newspaper that was established in 1945 and the role it played in raising political awareness among the Malay community in the Malay Peninsula. The final contribution discusses the discourse style of Al-Abrar, a novel by a local writer. It focuses on the writer's use of different forms of repetition in creating meaning and an impression on readers.